Peran Pendidikan Karakter dalam Pembentukan Sikap Positif pada Anak Usia 5–6 Tahun Di Lembaga Sekolah dalam Naungan Yayasan Santa Maria Blitar - Charmel Friani Palmisia Wae (UIN Fatmawati Sukarno Bengkulu, 2026)
Character education is an essential aspect of early childhood education because it serves as the foundation for children’s moral, social, and emotional development. Children aged 5–6 years are in a crucial developmental stage that greatly influences the formation of personality and positive attitudes in daily life. This study aims to describe the role of character education in shaping positive attitudes among children aged 5–6 years in schools under the auspices of the Santa Maria Blitar Foundation. This research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. The research subjects included teachers, principals, parents, and children aged 5–6 years. The results showed that character education plays a significant role in shaping children’s positive attitudes, such as honesty, helpfulness, politeness, respectfulness, and sportsmanship. Character education was implemented through habituation, exemplary behavior, interactive approaches, emotional involvement, routine school activities, and collaboration between schools and families. Teachers became the primary role models in demonstrating positive behavior to children. In addition, parental involvement and a supportive school culture strongly influenced the success of children’s character formation. This study concludes that consistent and continuous character education can effectively shape positive behavior in early childhood as the foundation for future social life.